2022
DOI: 10.1097/corr.0000000000002394
|View full text |Cite
|
Sign up to set email alerts
|

Is Social Deprivation Associated With Usage, Adverse Events, and Patient-reported Outcome Measures in Total Joint Arthroplasty? A Systematic Review

Abstract: BackgroundTo capture various social determinants of health, recent analyses have used comprehensive measures of socioeconomic disadvantage such as deprivation and vulnerability indices. Given that studies evaluating the effects of social deprivation on total joint arthroplasty (TJA) have yielded mixed results, a systematic review of this relationship might help answer questions about usage, complications, and results after surgery among patients in different socioeconomic groups and help guide targeted approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…In their article, Karimi et al [9] highlighted three key aspects of social deprivation as it relates to orthopaedic surgery and the field’s research. Foremost, social deprivation remains an undervalued variable in the perioperative treatment of patients undergoing arthroplasty and those undergoing orthopaedic surgery in general.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 3 more Smart Citations
“…In their article, Karimi et al [9] highlighted three key aspects of social deprivation as it relates to orthopaedic surgery and the field’s research. Foremost, social deprivation remains an undervalued variable in the perioperative treatment of patients undergoing arthroplasty and those undergoing orthopaedic surgery in general.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Foremost, social deprivation remains an undervalued variable in the perioperative treatment of patients undergoing arthroplasty and those undergoing orthopaedic surgery in general. Karimi et al [9] demonstrated that few studies examining social deprivation in arthroplasty have been performed; only 19 studies met the inclusion criteria for their review, which spanned a 22-year period. Focusing on social deprivation might improve access to care, increase the use of helpful interventions, and decrease the risk of complications after those interventions.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 2 more Smart Citations
“…Shared decision-making studies should focus on appropriate patient education regarding expectations, trajectory of functional recovery, and harnessing appropriate resources for social support. My colleagues and I have suggested linking patient data to deprivation measures such as the Area Deprivation Index to help encourage shared decision-making strategies that focus on health literacy and common barriers related to access [1]. Additionally, shared decision-making between patients with social deprivation and their providers or surgeons can improve the health literacy of these patients and subsequently ensure they have adequate access to quality care.…”
Section: How Do We Get There?mentioning
confidence: 99%